Maximal lactate steady state`s dependence on cycling cadence - Beneke, R.; Leithäuser, R. M. (International Journal of Sports Physiology and Performance, 2017)
The maximal lactate steady state (MLSS) depicts the highest blood lactate concentration (BLC) that can be maintained over time without a continual accumulation at constant prolonged workload. In cycling, no difference in the MLSS was combined with lower power output related to peak workload (IMLSS) at 100 than at 50 rpm. MLSS coincides with a respiratory exchange ratio (RER) close to 1. Recently, at incremental exercise, an RER of 1 was found at similar workload and similar intensity but higher BLC at 100 than at 50 rpm. Therefore, the authors reassessed a potential effect of cycling cadences on the MLSS and tested the hypothesis that the MLSS would be higher at 105 than at 60 rpm with no difference in IMLSS in a between-subjects design (n = 16, age 25.1 ± 1.9 y, height 178.4 ± 6.5 cm, body mass 70.3 ± 6.5 kg vs n = 16, 23.6 ± 3.0 y, 181.4 ± 5.6 cm, 72.5 ± 6.2 kg; study I) and confirmed these findings in a within-subject design (n = 12, 25.3 ± 2.1 y, 175.9 ± 7.7 cm, 67.8 ± 8.9 kg; study II). In study I, the MLSS was lower at 60 than at 105 rpm (4.3 ± 0.7 vs 5.4 ± 1.0 mmol/L; P = .003) with no difference in IMLSS (68.7% ± 5.3% vs 71.8% ± 5.9%). Study II confirmed these findings on MLSS (3.4 ± 0.8 vs 4.5 ± 1.0 mmol/L; P = .001) and IMLSS (65.0% ± 6.8% vs 63.5% ± 6.3%; P = .421). The higher MLSS at 105 than at 60 rpm combined with an invariance of IMLSS and RER close to 1 at MLSS supports the hypothesis that higher cadences can induce a preservation of carbohydrates at given BLC levels during low-intensity, high-volume training sessions.